Haematological Parameters in Preterm Neonates Admitted in Neonatal Intensive Care Unit in a Tertiary Care Hospital - Dwepa Kamlesh Parikh; Amit Ravindra Nisal; Ravindra Chandrashekhar Nimbargi (Medical Laboratory Technology Journal, 2023)
Though reference haematological parameters are defined for neonates, ranges vary in preterm. Few data are available regarding the premature population during the first month of life. Objective: To observe the variation in haematological parameters concerning different gestational ages, birth weights and gender among preterm neonates admitted to NICU with common illnesses like respiratory distress (RDS), neonatal hyperbilirubinemia (NNH) and sepsis in a tertiary care hospital. A total of ninety preterm neonates admitted to the neonatal intensive care unit (NICU) were analyzed over two years. Complete blood counts were obtained, grouped and analyzed according to the underlying diagnosis of sepsis, NNH and RDS. Clinical data were also extracted. The data were analyzed using SPSS software version 25. Mean, Chi-square test and ANOVA tests were used for data analysis. P value <0.05 was considered significant. Result: Variation was seen concerning gestational age and birth weight. Eosinophils were significantly decreased in LBW, while a decrease in neutrophils and an increase in lymphocyte count were seen in EPT. Haemoglobin and RBC indices also showed significant variation according to birth weight. Conclusions research complete blood counts of preterm depend on the degree of prematurity, birth weight, and other clinical findings.